Cathode active material for lithium secondary battery, and cathode for lithium secondary battery and lithium secondary battery including the same
Patent Information
- Application Number
- KR1020210175545
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-09
- Publication Date
- 2026-09-02
- Estimated Expiration
- 2041-12-09
Smart Images

Figure 112021142802116-PAT00002_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the same. More specifically, the invention relates to a positive electrode active material of the lithium metal oxide series, and a positive electrode and a lithium secondary battery comprising the same. Background Technology
[0003] Rechargeable batteries are batteries capable of repeated charging and discharging, and with the advancement of the information and communication and display industries, they are widely applied as power sources for portable electronic communication devices such as camcorders, mobile phones, and laptop PCs. Furthermore, recently, battery packs containing rechargeable batteries are being developed and applied as power sources for eco-friendly vehicles, such as hybrid cars.
[0004] Examples of secondary batteries include lithium-ion batteries, nickel-cadmium batteries, and nickel-hydrogen batteries; among these, active research and development is being conducted on lithium-ion batteries due to their high operating voltage and energy density per unit weight, as well as their advantages in charging speed and weight reduction.
[0005] A lithium secondary battery may include an electrode assembly comprising a positive electrode, a negative electrode, and a separator, and an electrolyte impregnating the electrode assembly. The lithium secondary battery may further include an outer casing, for example, in the form of a pouch, that accommodates the electrode assembly and the electrolyte.
[0006] As the application range of lithium secondary batteries expands to large devices such as hybrid vehicles, high-nickel lithium oxides with a higher nickel content are known as cathode active materials for securing high capacity in lithium secondary batteries.
[0007] However, in generally known high-nickel lithium oxides, the lifespan and operational stability of lithium secondary batteries can be degraded due to the occurrence of cation disorders in which nickel ions exist at lithium ion positions.
[0008] For example, Korean Registered Patent Publication No. 10-0821523 discloses a positive electrode active material comprising a high-nickel lithium composite oxide, but as described above, there are limitations in ensuring sufficient lifespan and operational stability. Prior art literature
[0010] Korean Registered Patent Publication No. 10-0821523 The problem to be solved
[0011] One objective of the present invention is to provide a positive electrode active material for a lithium secondary battery having excellent operational stability and capacity retention characteristics.
[0012] One objective of the present invention is to provide a positive electrode for a lithium secondary battery and a lithium secondary battery with improved operational stability and capacity retention characteristics. means of solving the problem
[0014] A positive electrode active material for a lithium secondary battery according to exemplary embodiments comprises a first positive electrode active material having a sphericity of 0.9 to 0.96 and a second positive electrode active material having a sphericity smaller than that of the first positive electrode active material, and the content of the second positive electrode active material may be smaller than the content of the first positive electrode active material.
[0015] For example, the mixing weight ratio of the first positive active material and the second positive active material may be 9:1 to 6:4.
[0016] In some embodiments, the first positive electrode active material and the second positive electrode active material may each independently comprise lithium metal oxide particles represented by the following chemical formula 1.
[0017] [Chemical Formula 1]
[0018] Li xNi y M1 1-y O z
[0019] In the above chemical formula 1, M1 may be at least one element selected from the group consisting of B, Al, Si, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Y, Zr, Mo, Sn, and W, and x is 0 <x<≤1.1, y는 0.8≤y≤0.98, z는 2.0≤z≤2.02일 수 있다.
[0020] In one embodiment, in the above formula 1, y may be 0.8≤y≤0.95.
[0021] In some embodiments, the average sphericity of the positive electrode active material for the lithium secondary battery may be 0.9 to 0.96. The average sphericity refers to the arithmetic mean value of the sphericity of all particles constituting the positive electrode active material for the lithium secondary battery.
[0022] In some embodiments, the sphericity of the second positive active material may be less than 0.96, for example, 0.9 or greater and less than 0.96.
[0023] According to exemplary embodiments, the difference in sphericity between the first positive active material and the second positive active material may be 0.01 or greater, specifically 0.01 to 0.02.
[0024] For example, the sphericity of the first positive active material may be 0.95 to 0.96, and the sphericity of the second positive active material may be 0.9 to 0.95.
[0025] In some embodiments, the first positive electrode active material may have a polycrystalline structure. For example, the first positive electrode active material may be a polycrystalline particle.
[0026] In some embodiments, the second positive active material may have a single-crystal structure. For example, the second positive active material may be a single-crystal particle.
[0027] In some embodiments, the average particle size (D50) of the first positive active material may be larger than the average particle size of the second positive active material. For example, the average particle size (D50) of the first positive active material may be 8 to 20 μm, and the average particle size of the second positive active material may be 2 to 8 μm.
[0028] In some embodiments, the first positive active material may have a secondary particle structure, and the second positive active material may have a single particle structure.
[0029] In some embodiments, the positive electrode active material for the lithium secondary battery may have a tap density of 3.66 g / cc or more when pressurized at 20 MPa, for example, 3.66 to 4.0 g / cc.
[0030] A positive electrode for a lithium secondary battery according to exemplary embodiments comprises a positive electrode active material layer comprising the positive electrode active material for a lithium secondary battery described above. For example, it may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.
[0031] In some embodiments, the electrode density of the positive active material layer may be 2.5 to 4.0 g / cc.
[0032] A lithium secondary battery according to exemplary embodiments comprises a positive electrode comprising the positive electrode active material for a lithium secondary battery described above, and a negative electrode facing the positive electrode. Effects of the invention
[0034] A positive electrode active material for a lithium secondary battery according to exemplary embodiments may include heterogeneous positive electrode active material particles with different sphericities in a predetermined content ratio. By including heterogeneous positive electrode active material particles with different sphericities, the packing properties of the positive electrode active material can be improved, and a decrease in electrode density and energy density can be prevented. In addition, the positive electrode active material may have a high sphericity; in this case, the structural stability of the positive electrode active material is improved, and the initial capacity and battery efficiency characteristics of the lithium secondary battery can be improved.
[0035] In addition, the heterogeneous cathode active material particles may each have polycrystalline and single-crystal structures. In this case, the electrochemical performance of the cathode active material can be improved by polycrystalline particles having a relatively high degree of sphericity. Furthermore, the structural stability of the cathode active material can be further improved by single-crystal particles having a relatively low degree of sphericity.
[0036] In addition, the above heterogeneous cathode active materials may each contain a high amount of nickel and be lithium metal oxides in which lithium nickel and a transition metal are bonded within a predetermined range. In this case, the structure of the active material is stabilized while maintaining the high capacity characteristics of the cathode active material, thereby improving lifespan and operational stability. Brief explanation of the drawing
[0038] FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view, respectively, showing a lithium secondary battery according to exemplary embodiments. Figures 3a and 3b are graphs showing the sphericity distribution of the first positive active material and the second positive active material of Example 1, respectively. Figures 4a and 4b are Scanning Electron Microscopy (SEM) images of cross-sections of a positive electrode for a lithium secondary battery according to Example 1 and Example 2, respectively. FIGS. 5a to 5c are SEM images of cross-sections of positive electrodes for lithium secondary batteries according to Comparative Examples 1 to 3, respectively. Specific details for implementing the invention
[0039] Embodiments of the present invention provide a positive electrode active material for a lithium secondary battery comprising heterogeneous lithium metal oxide particles of different sphericities in a predetermined mixing weight ratio, and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the same.
[0040] The term "lithium metal oxide" as used in this application refers to a composite oxide comprising lithium and at least one alkali metal, alkaline earth metal, transition metal, post-transition metal, or metalloid other than lithium.
[0041] Hereinafter, embodiments of the present invention will be described in detail.
[0042] Cathode active material for lithium secondary batteries
[0043] Embodiments of the present invention will be described in more detail below with reference to the drawings. However, the following drawings attached to this specification are intended to illustrate some embodiments of the present invention and serve to further enhance understanding of the technical concept of the present invention together with the content of the invention to be described below; therefore, the present invention should not be interpreted as being limited only to the matters described in such drawings.
[0044] A positive electrode active material for a lithium secondary battery according to exemplary embodiments may include a first positive electrode active material having a circularity of 0.9 to 0.96, and a second positive electrode active material having a circularity smaller than that of the first positive electrode active material.
[0045] The sphericity of the first positive active material may refer to the sphericity of particles at 50% of the volume fraction of 10,000 positive active material particles included in the first positive active material. The sphericity of the second positive active material may refer to the sphericity of particles at 50% of the volume fraction of 10,000 positive active material particles included in the second positive active material.
[0046] For example, the first positive active material and the second positive active material may include positive active material particles with a spherical shape. A perfect sphere has a sphericity value of 1, and the closer the sphericity value of the particle is to 1, the closer the shape of the particle becomes to a perfect sphere.
[0047] For example, the sphericity of a particle can be calculated as the square of the ratio of the circumference of a circle having the same area as the particle to the circumference of the particle. For example, the sphericity of a particle can be calculated using the following mathematical formula 1.
[0048] [Mathematical Formula 1]
[0049] Circularity = 4πA / P 2
[0050] In the above mathematical formula 1, A is the area of the particle, and P is the perimeter of the particle.
[0051] The area and perimeter of the particle can be measured by observing a cross-section of the active material with a scanning electron microscope (SEM) and using image analysis software such as Image J from the obtained image. Alternatively, the sphericity of the particle can be measured by a flow particle image analyzer.
[0052] As the positive active material according to exemplary embodiments includes heterogeneous particles with different sphericities, more particles can be packaged in a given space. For example, second positive active material particles with a small sphericity can be uniformly dispersed and distributed among first positive active material particles with a large sphericity. In this case, damage to the positive active material particles due to excessive pressure or compression can be prevented, and a high packing density can be achieved. Accordingly, the energy density per unit volume of the electrode can be increased.
[0053] In some embodiments, the sphericity of the second positive active material may be less than 0.96, preferably 0.9 or higher and less than 0.96. Within this range, the positive active material for a lithium secondary battery may have a high overall sphericity, and structural stability may be improved. For example, if the sphericity of the second positive active material is less than 0.9, the strength of the particles is reduced, and particle breakage or damage may occur during high-voltage driving and charge / discharge behavior. For example, if the sphericity of the second positive active material is 0.96 or higher, the packing properties of the positive active material may be reduced, and charge / discharge capacity and electrochemical performance may decrease.
[0054] According to exemplary embodiments, the average sphericity of the positive electrode active material for the lithium secondary battery may be 0.9 to 0.96. Specifically, the average sphericity of the positive electrode active material for the lithium secondary battery may be 0.95 to 0.96, preferably 0.955 to 0.960, and more preferably 0.955 or higher and less than 0.960. The average sphericity of the positive electrode active material for the lithium secondary battery may refer to the arithmetic mean value of the sphericity of the first positive electrode active material and the sphericity of the second positive electrode active material.
[0055] Within the above range, the mechanical and electrical stability of the positive electrode active material can be improved, and accordingly, the lifespan stability and capacity retention characteristics of the positive electrode and secondary battery can be enhanced.
[0056] For example, as the average sphericity is 0.95 or higher, the positive electrode active material is structurally stable, which can prevent breakage and defects of the active material particles caused by repeated charging and discharging and physical impact. In addition, a high average sphericity of the positive electrode active material can increase the contact area between active material particles during electrode rolling. In this case, the movement of ions / electrons through the boundaries between active material particles can be facilitated, and the adhesion between active material particles can be increased.
[0057] For example, as the average sphericity of the positive electrode active material for a lithium secondary battery is 0.96 or less, the decrease in electrode density due to the structural characteristics of spherical particles can be prevented, and the charge / discharge capacity and initial efficiency of the secondary battery can be improved.
[0058] In addition, the packing density of the cathode active material can be further increased by including heterogeneous cathode active material particles with different sphericities. For example, while the closer the sphericity of the cathode active material particles is to 1, the more structurally stable they can be, the less packing properties the particles have during the pressing process, which may lead to a decrease in electrode density. In this case, the energy density per unit volume decreases, which may result in reduced capacity characteristics and initial efficiency.
[0059] In some embodiments, the difference in sphericity between the first positive active material and the second positive active material may be 0.01 or greater. Within this range, high electrode density can be achieved during rolling while maintaining the structural stability of the positive active material.
[0060] Specifically, the difference in sphericity between the first positive active material and the second positive active material may be 0.01 to 0.02, and preferably 0.01 to 0.015. If the difference in sphericity between the first positive active material and the second positive active material is less than 0.01, the packing properties of the particles decrease, and the capacity per unit volume may decrease. If the difference in sphericity between the first positive active material and the second positive active material is greater than 0.02, the overall sphericity of the positive active material may decrease, which may reduce structural stability and consequently reduce the lifespan performance of the electrode.
[0061] For example, the sphericity of the first positive active material may be 0.95 to 0.96, and the sphericity of the second positive active material may be 0.9 to 0.95. When the first positive active material and the second positive active material have the sphericity described above, the positive active material for a lithium secondary battery may have a high overall average sphericity, and the filling density may increase. Accordingly, the mechanical and electrochemical stability of the electrode may be improved, while the capacity and output characteristics may be enhanced.
[0062] According to exemplary embodiments, the positive electrode active material for a lithium secondary battery may include lithium metal oxide particles represented by the following chemical formula 1. For example, the first positive electrode active material and the second positive electrode active material may each independently include lithium metal oxide particles represented by the following chemical formula 1.
[0063] [Chemical Formula 1]
[0064] Li x Ni y M1 1-y O z
[0065] In the above chemical formula 1, M1 may be at least one element selected from the group consisting of B, Al, Si, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Y, Zr, Mo, Sn, and W. x is 0 <x≤1.1, y는 0.8≤y≤0.98, z는 2.0≤z≤2.02일 수 있다.
[0066] For example, the first positive electrode active material and the second positive electrode active material may include lithium-nickel composite metal oxide particles containing a high amount of nickel and containing lithium, nickel, and metal elements other than nickel in a predetermined range.
[0067] The term "excess" as used in this application refers to inclusion in the largest content or molar ratio among the metals excluding lithium. The terms "content" or "concentration" as used in this application may refer to the molar ratio in lithium metal oxides.
[0068] In some embodiments, the molar ratio or concentration (x) of Ni in Formula 1 may be 0.8 or higher and 0.98 or lower. If the Ni concentration is less than about 0.8, a sufficiently high-capacity lithium secondary battery may not be realized. Additionally, the capacity increase effect resulting from the insertion of M1 described below may not be substantially realized. If the Ni concentration exceeds about 0.98, the stability of the cathode active material is excessively reduced, which may lead to reduced lifespan and mechanical instability.
[0069] Preferably, in Formula 1, the molar ratio or concentration of Ni may be 0.8 to 0.95, or 0.8 to 0.9. For example, in Formula 1, y may be 0.8 ≤ y ≤ 0.95. In this case, it is possible to maintain a high capacity while preventing side reactions and structural degradation of the cathode active material.
[0070] For example, Ni can be provided as a metal associated with the capacity of a lithium secondary battery. Accordingly, by employing a composition containing a high content of Ni in the lithium metal oxide particles as described above, a high-capacity cathode and a lithium secondary battery are provided, and the output can also be increased.
[0071] As mentioned above, while a higher Ni content can improve the capacity of lithium secondary batteries, it may be disadvantageous in terms of lifespan characteristics and mechanical and electrical stability. For example, if the Ni content increases excessively, defects such as ignition or short circuits may not be sufficiently suppressed in the event of penetration by external objects. Furthermore, as particle strength decreases, fracture or breakage may occur when excessive pressure is applied, which may limit the ability to increase electrode density.
[0072] The cathode active material for a lithium secondary battery according to exemplary embodiments has a high average sphericity, which can improve structural stability and particle strength. Accordingly, a high packing density can be achieved, and damage or breakage of the active material particles can be prevented even when used in high-voltage batteries. Therefore, a secondary battery with high capacity and high output can be provided, and the cycle life can also be increased.
[0073] In some embodiments, chemical and mechanical instability caused by Ni can be improved by distributing M1 together with lithium metal oxide particles. For example, M1 may include Co and Mn, and in one embodiment, may further include Al.
[0074] For example, Mn can be provided as a metal related to the mechanical and electrical stability of lithium secondary batteries. Mn can suppress or reduce defects such as ignition and short circuits that occur when the anode is penetrated by an external object, and can increase the lifespan of the lithium secondary battery. Additionally, Co can improve the conductivity of lithium-nickel composite metal oxide particles and reduce resistance, thereby improving the output of the secondary battery.
[0075] As described above, when lithium metal oxide particles contain Ni, Co, Mn, Al, etc., the oxidation states of Co and Al can be fixed at +3, and the oxidation state of Mn can be fixed at +4. The oxidation state of Ni can have a variable oxidation state ranging from +2 to +4 depending on the synthesis conditions and the operating environment of the secondary battery.
[0076] In some embodiments, the lithium metal oxide particles may further include a metal element having an elemental size similar to nickel and an oxidation state of +2. For example, they may further include Be, Mg, Ca, Sr, Ba, and / or Ra.
[0077] In this case, at least one element having a +2 oxidation state is included to suppress the transition or substitution of +2 valence Ni to lithium sites. Accordingly, the occurrence of cation disorders in which Ni ions exist or transition to Li ion positions is suppressed, and lifespan stability and capacity retention characteristics can be improved.
[0078] For example, the first positive electrode active material and the second positive electrode active material may include lithium metal oxide particles represented by the following chemical formula 2.
[0079] [Chemical Formula 2]
[0080] Li x Ni y M1 1-y M2 a O z
[0081] In the above chemical formula 2, M1, x, y, and z are the same as in the above chemical formula 1, and M2 may be at least one element selected from the group consisting of Be, Mg, Ca, Sr, Ba, and Ra. a may be a molar ratio of M2 weight that is greater than 0% and less than 2.5% of Ni weight, for example, a may be 0.0002≤a≤0.02.
[0082] If the content of M2 exceeds 2.5 weight% of the weight of Ni, the amount of Ni ions present at the lithium ion positions exceeds the amount corresponding to defects, which can increase the initial resistance of the lithium secondary battery and decrease the discharge capacity.
[0083] In some embodiments, the first positive electrode active material may have a polycrystalline structure. For example, the first positive electrode active material may include particles having a polycrystalline structure, and specifically may be composed of polycrystalline particles. A polycrystalline structure may mean having several small individual crystals separated from each other by grain boundaries within the particles.
[0084] As the first positive electrode active material, which has a relatively high degree of sphericity, has a polycrystalline structure, a pathway for the movement of lithium ions through grain boundaries can be secured. Accordingly, the structural stability of the positive electrode active material is improved, while the capacity characteristics and fast charging characteristics of the battery can be enhanced.
[0085] In some embodiments, the second positive active material may have a single crystal structure. For example, the second positive active material may include particles having a single crystal structure, and specifically may be composed of single crystal particles. A single crystal structure may mean having only one crystal within the particle.
[0086] Since the single-crystal structure contains only one crystal within a single grain, cracking and collapse of the grain caused by the rolling process and repeated charging and discharging can be prevented. Therefore, by having a single-crystal structure with a homo-orientation for the second positive active material, the structural stability of the positive active material is improved, and consequently, the lifespan and operational stability of the lithium secondary battery can be enhanced.
[0087] In one embodiment, the second positive active material may be arranged in a direction parallel to the 001 crystal plane. Since the crystal direction of the second positive active material is regularly oriented, the movement path of lithium ions may be reduced, and accordingly, ion / electrical conductivity may be improved.
[0088] According to exemplary embodiments, the content of the second positive active material may be smaller than the content of the first positive active material. For example, the first positive active material may be included in excess of the positive active material for a lithium secondary battery. In this case, the filling density and packing properties may be improved while preventing a decrease in the mechanical strength and structural stability of the positive active material.
[0089] In some embodiments, the mixing weight ratio of the first positive active material and the second positive active material may be 9.5:0.5 to 5.5:4.5. Within this range, the positive active material for a lithium secondary battery may have a high average sphericity, and the packing efficiency between active material particles may be improved. Accordingly, high energy density is provided, and at the same time, the cycle life characteristics of the secondary battery may be improved.
[0090] Preferably, the mixing weight ratio of the first positive active material and the second positive active material may be 9:1 to 6:4, and for example, the mixing weight ratio of the first positive active material and the second positive active material may be 8:2. In this case, the high power characteristics and lifespan characteristics of the secondary battery may be further improved.
[0091] According to exemplary embodiments, the first positive active material may have a secondary particle structure, and the second positive active material may have a single particle structure. For example, the first positive active material may have a polycrystalline secondary particle structure or shape formed by aggregating or assembling a plurality of primary particles. For example, the second positive active material may have a single-crystal single particle structure.
[0092] As the first positive active material with relatively high sphericity has a secondary particle structure in which individual primary particles are aggregated, the high sphericity prevents the occurrence of cracks inside the particles while promoting the movement of lithium ions between the individual primary particles. In this case, the charge / discharge speed can be improved, and capacity retention characteristics can be improved.
[0093] As the second positive active material with relatively low sphericity has a single-particle structure, the packing properties of the electrode are improved due to the low sphericity, while preventing the occurrence of cracks inside the particles, thereby improving the battery's lifespan characteristics and long-term operational stability.
[0094] According to exemplary embodiments, the average particle size (D50) of the second positive active material may be smaller than the average particle size (D50) of the first positive active material. The average particle size (D50) refers to the longest diameter of a particle at a volume fraction of 50% in the cumulative particle size distribution. In this case, the second positive active material particles with low sphericity may be uniformly distributed among the first positive active material particles with relatively high sphericity, thereby improving the packing properties of the positive active material for a lithium secondary battery.
[0095] In some embodiments, the average particle size (D50) of the first positive active material may be 8 to 20 μm. Preferably, it may be 10 to 20 μm, and more preferably, 10 to 18 μm. For example, if the average particle size of the first positive active material having a polycrystalline structure is less than 8 μm, the tap density of the active material may decrease. For example, if the average particle size of the first positive active material is greater than 20 μm, the diffusion path of lithium ions becomes longer, and electrochemical properties may decrease.
[0096] In some embodiments, the average particle size (D50) of the second positive active material may be 2 to 8 μm. Preferably, it may be 2 to 3.5 μm. For example, if the average particle size of the second positive active material having a single crystal structure is less than 2 μm, the tap density and stability of the active material may decrease. For example, if the average particle size of the second positive active material is greater than 8 μm, the distribution of active material particles is not uniform, so the tap density may decrease and the diffusion path of lithium ions may become longer.
[0097] In addition, as the second positive active material is filled between the first positive active material within the above average particle size, the filling density of the electrode can be increased. In this case, the thickness of the electrode can be reduced, and since the pressure required to achieve high electrode density and thin electrode thickness is reduced, the breaking of the positive active material particles due to excessive pressure can be prevented.
[0098] In some embodiments, the tap density of the positive electrode active material for the lithium secondary battery may be 3.66 g / cc or higher when pressurized at 20 MPa. For example, the tap density can be measured by placing 100 g of the positive electrode active material for the lithium secondary battery into a 100 ml graduated cylinder and tapping it 1,000 times at a pressure of 20 MPa. Specifically, the tap density may be 3.66 to 4.0 g / cc, and more specifically, 3.70 to 4.0 g / cc.
[0099] As described above, by including heterogeneous lithium metal oxide particles with different sphericities in the positive electrode active material, a high tap density can be provided even at low pressure during the press process for electrode manufacturing, for example. In this case, the initial charge / discharge capacity can be increased while preventing structural collapse and defects of the positive electrode active material caused by excessive pressure.
[0100] <Cathode for Lithium Secondary Batteries and Lithium Secondary Batteries>
[0101] FIGS. 1 and FIGS. 2 are a schematic plan view and a cross-sectional view illustrating a lithium secondary battery according to exemplary embodiments.
[0102] Hereinafter, a lithium secondary battery comprising a positive electrode including a positive electrode active material for a lithium secondary battery as described above with reference to FIG. 1 and FIG. 2 is provided.
[0103] Referring to FIGS. 1 and 2, a lithium secondary battery may include a positive electrode (100) comprising a positive electrode active material layer comprising the positive electrode active material for the lithium secondary battery described above, and a negative electrode (130) facing the positive electrode.
[0104] The positive electrode (100) may include a positive electrode active material layer (110) formed by applying the above-described positive electrode active material to a positive electrode current collector (105).
[0105] For example, a slurry can be prepared by mixing and stirring a positive active material with a binder, a conductive material and / or a dispersant, etc., in a solvent. A positive electrode can be prepared by coating the slurry onto a positive current collector (105), and then compressing and drying it.
[0106] The positive current collector (105) may include, for example, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof, and preferably may include aluminum or an aluminum alloy.
[0107] The above binder may include, for example, organic binders such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidenefluoride (PVDF), polyacrylonitrile, and polymethylmethacrylate, or water-based binders such as styrene-butadiene rubber (SBR), and may be used together with a thickener such as carboxymethyl cellulose (CMC).
[0108] For example, a PVDF-based binder can be used as a binder for forming the positive electrode. In this case, the amount of binder for forming the positive electrode active material layer (110) can be reduced and the amount of the positive electrode active material can be increased relatively, thereby improving the output and capacity of the secondary battery.
[0109] The above conductive material may be included to promote electron transfer between active material particles. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, graphene, carbon nanotubes, etc., and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, etc.
[0110] In some embodiments, the electrode density of the positive electrode (100) may be 2.5 to 4.0 g / cc, and preferably 3.2 to 3.8 g / cc. For example, electrode density may mean the value obtained by dividing the total weight of the positive electrode active material layer (110) by the total volume of the positive electrode active material layer (110).
[0111] If the electrode density of the positive electrode (100) is less than 2.5 g / cc, the energy density per unit volume is lowered, so the charge / discharge capacity and high-speed charging characteristics of the secondary battery may be degraded. If the electrode density of the positive electrode (100) is greater than 4.0 g / cc, cracks and damage to the positive electrode active material may increase as excessive pressure is required during the rolling process.
[0112] In some embodiments, the anode (100) may have an electrode density of 3.66 g / cc or more when pressurized at 20 MPa, and preferably 3.70 to 4.0 g / cc. By including heterogeneous lithium metal oxide particles with different sphericities, a high electrode density can be secured without excessive pressure, and accordingly, the charge / discharge and lifespan characteristics of the electrode may be excellent.
[0113] The negative electrode (130) may include a negative electrode current collector (125) and a negative electrode active material layer (120) formed by coating a negative electrode active material onto the negative electrode current collector (125).
[0114] The above-mentioned negative electrode active material may be any material known in the art capable of absorbing and extracting lithium ions without special limitation. For example, carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers; lithium alloys; silicon or tin, etc. may be used. Examples of the above-mentioned amorphous carbon include hard carbon, coke, mesocarbon microbeads (MCMB) calcined at 1500°C or lower, and mesophase pitch-based carbon fibers (MPCF). Examples of the above-mentioned crystalline carbon include graphite-based carbon such as natural graphite, graphitized coke, graphitized MCMB, and graphitized MPCF. Elements included in the above-mentioned lithium alloy may include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium.
[0115] The negative current collector (125) may include, for example, gold, stainless steel, nickel, aluminum, titanium, copper, or an alloy thereof, and preferably may include copper or a copper alloy.
[0116] In some embodiments, the cathode active material may be mixed and stirred with a binder, a conductive material and / or a dispersant, etc., in a solvent to prepare a slurry. The cathode (130) may be prepared by coating the slurry onto the cathode current collector, and then compressing and drying it.
[0117] Materials substantially identical or similar to the materials described above may be used as the binder and conductive material. In some embodiments, the binder for forming the cathode may include, for example, a water-based binder such as styrene-butadiene rubber (SBR) for compatibility with carbon-based active materials, and may be used together with a thickener such as carboxymethyl cellulose (CMC).
[0118] In some embodiments, the electrode density of the cathode (120) may be 1.4 to 1.9 g / cc.
[0119] A separator (140) may be interposed between the anode (100) and the cathode (130). The separator (140) may include a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, an ethylene / methacrylate copolymer, etc. The separator (140) may also include a nonwoven fabric formed of high-melting-point glass fibers, polyethylene terephthalate fibers, etc.
[0120] According to exemplary embodiments, an electrode cell is defined by an anode (100), a cathode (130), and a separator (140), and a plurality of said electrode cells may be stacked to form, for example, an electrode assembly (150) in the form of a jelly roll. For example, the electrode assembly (150) may be formed by winding, laminating, folding, etc., of the separator (140).
[0121] The above electrode assembly may be housed together with an electrolyte within an outer case (160) to define a lithium secondary battery. According to exemplary embodiments, a non-aqueous electrolyte may be used as the electrolyte.
[0122] The non-aqueous electrolyte comprises a lithium salt as an electrolyte and an organic solvent, and the lithium salt is, for example, Li + X -It is expressed as and the anion (X) of the above lithium salt - As F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - Examples of the back can be given.
[0123] Examples of the above organic solvents may include propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylmethyl carbonate (EMC), methylpropyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, vinylene carbonate, sulfolane, gamma-butyrolactone, propylene sulfite, and tetrahydrofuran. These may be used individually or in combination of two or more.
[0124] As illustrated in FIG. 2, electrode tabs (positive tabs and negative tabs) may protrude from the positive current collector (105) and negative current collector (125) belonging to each electrode cell and extend to one side of the outer case (160). The electrode tabs may be fused together with the one side of the outer case (160) to form electrode leads (positive lead (107) and negative lead (127)) that extend or are exposed to the outside of the outer case (160).
[0125] The above lithium secondary battery can be manufactured in, for example, a cylindrical, prismatic, pouch, or coin type using a can.
[0126] According to exemplary embodiments, the chemical and structural stability of the cathode active material can be improved and the packing properties can be excellent by including heterogeneous lithium metal oxide particles with different sphericities and having a high average sphericity. Accordingly, a lithium secondary battery with improved lifespan and long-term stability can be realized while suppressing the reduction in capacity and average voltage.
[0128] Hereinafter, preferred embodiments are presented to aid in understanding the present invention; however, these embodiments are merely illustrative of the invention and are not intended to limit the appended claims. It is obvious to those skilled in the art that various changes and modifications to the embodiments are possible within the scope and spirit of the invention, and that such variations and modifications fall within the scope of the appended claims.
[0130] Examples and Comparative Examples
[0131] (1) Preparation of positive electrode active material
[0132] 1) Preparation Example 1: Preparation of the first positive electrode active material
[0133] NiSO4, CoSO4, and MnSO4 were mixed in the ratios (molar ratios) shown in Table 1 below using distilled water from which internal dissolved oxygen had been removed by bubbling with N2 for 24 hours. The above solution was introduced into a reactor at 50°C, and a co-precipitation reaction was carried out for 48 hours using NaOH and NH3H2O as a precipitating agent and a chelating agent to form nickel-cobalt-manganese hydroxide (complex metal salt compound) with a particle size of approximately 10 to 20 μm. At this time, the pH was controlled by adjusting the concentration and input amount of NaOH and NH3H2O to ensure uniform crystal growth. The complex metal salt compound was dried at 80°C for 12 hours, and then re-dried at 110°C for 12 hours.
[0134] Subsequently, lithium hydroxide was added so that the ratio of the complex metal salt compound to lithium hydroxide was 1:1.05, and the mixture was uniformly stirred and mixed for 5 minutes. The mixture was placed in a calcination furnace and heated to 710°C at a heating rate of 2°C / min, and maintained at 710°C for 10 hours. During the heating and maintenance, oxygen was continuously passed through at a flow rate of 10 mL / min. After the calcination was completed, the mixture was naturally cooled to room temperature, followed by grinding and classification. At this time, the mixture was ground using a ball mill with zirconia balls, and polycrystalline lithium metal oxide particles having the sphericity shown in Table 1 below were obtained by adjusting the ball size and time.
[0135] The composition and sphericity of the obtained lithium metal oxide particles are shown in Table 1 below (for example, the chemical formula of the first cathode active material of Example 5 is LiNi 0.8 Co 0.1 Mn 0.1 O2). At this time, the molar ratio of oxygen is fixed at 2.0.
[0136] 2) Preparation Example 2: Preparation of the second positive electrode active material
[0137] Single-crystal lithium metal oxide particles were obtained by performing the same process as in Preparation Example 1, except that the pH was controlled by adjusting the concentration and input amount of NaOH and NH3H2O during the preparation of nickel-cobalt-manganese hydroxide to obtain single-crystal particles.
[0138] The composition and sphericity of the obtained lithium metal oxide particles are shown in Table 1 below. At this time, the molar ratio of oxygen is fixed at 2.0.
[0139] 3) Sphericity measurement
[0140] The sphericity of the above-prepared cathode active material was measured using a sphericity analyzer (Morphologi 4, Malvern Panalytical). Specifically, a 1 mm sample of the above-prepared cathode active material 3After dispersing under conditions of 4 bar and 10 ms, the positive active material particles were analyzed using a two-dimensional image. Subsequently, the sphericity corresponding to 50% of the volume of 10,000 positive active material particles was measured.
[0142] division First positive active material Second positive active material Average sphericity Composition (Ni : Co : Mn) Spherical shape Content Composition (Ni : Co : Mn) Spherical shape Content Example 1 8.8 : 0.9 : 0.3 0.960 90 8.8 : 0.9 : 0.3 0.944 10 0.958 Example 2 8.8 : 0.9 : 0.3 0.960 80 8.8 : 0.9 : 0.3 0.944 20 0.957 Example 3 8.8 : 0.9 : 0.3 0.960 70 8.8 : 0.9 : 0.3 0.944 30 0.955 Example 4 8.8 : 0.9 : 0.3 0.960 60 8.8 : 0.9 : 0.3 0.944 40 0.954 Example 5 8 : 1 : 1 0.962 80 8 : 1 : 1 0.945 20 0.959 Example 6 8 : 1 : 1 0.962 80 8.3 : 1.1 : 0.6 0.945 20 0.959 Example 7 8.3 : 1.1 : 0.6 0.959 80 8.3 : 1.1 : 0.6 0.945 20 0.956 Example 8 8.3 : 1.1 : 0.6 0.959 80 8.8 : 0.9 : 0.3 0.944 20 0.956 Example 9 9.4 : 0.3 : 0.3 0.960 80 8.8 : 0.9 : 0.3 0.944 20 0.957 Example 10 9.4 : 0.3 : 0.3 0.960 80 9.4 : 0.3 : 0.3 0.943 20 0.957 Example 11 9.4 : 0.3 : 0.3 0.960 80 9.8 : 0.1 : 0.1 0.941 20 0.956 Example 12 9.8 : 0.1 : 0.1 0.958 80 9.8 : 0.1 : 0.1 0.941 20 0.955 Example 13 8.8 : 0.9 : 0.3 0.949 80 8.8 : 0.9 : 0.3 0.945 20 0.948 Example 14 8.8 : 0.9 : 0.3 0.960 80 8.8 : 0.9 : 0.3 0.951 20 0.958 Example 15 8.8 : 0.9 : 0.3 0.962 80 8.8 : 0.9 : 0.3 0.941 20 0.958 Comparative Example 1 8.8 : 0.9 : 0.3 0.960 100 - - - 0.960 Comparative Example 2 8.8 : 0.9 : 0.3 0.960 50 8.8 : 0.9 : 0.3 0.944 50 0.952 Comparative Example 3 8.8 : 0.9 : 0.3 0.960 40 8.8 : 0.9 : 0.3 0.944 60 0.950 Comparative Example 4 8.8 : 0.9 : 0.3 0.960 30 8.8 : 0.9 : 0.3 0.944 70 0.949 Comparative Example 5 8.8 : 0.9 : 0.3 0.960 20 8.8 : 0.9 : 0.3 0.944 80 0.947 Comparative Example 6 8.8 : 0.9 : 0.3 0.960 10 8.8 : 0.9 : 0.3 0.944 90 0.946 Comparative Example 7 - - - 8.8 : 0.9 : 0.3 0.944 100 0.944
[0144] Figures 3a and 3b are graphs showing the sphericity distribution of the first positive active material and the second positive active material of Example 1, respectively.
[0145] Referring to FIGS. 3a and 3b, it can be seen that the sphericity corresponding to 50% of the volume of the first positive active material of Example 1 is 0.960, and the sphericity corresponding to 50% of the volume of the second positive active material of Example 1 is 0.944.
[0147] (2) Manufacturing of secondary batteries
[0148] A secondary battery was manufactured using the positive active materials of the examples and comparative examples listed in Table 1. Specifically, a positive composite was prepared by mixing the positive active material, Denka Black as a conductive material, and PVDF as a binder in a mass ratio composition of 94:3:3, respectively, and then the positive was manufactured by coating and drying it on an aluminum current collector and then rolling it at a pressure of 20 MPa.
[0149] A cathode slurry was prepared comprising 93 wt% natural graphite as a cathode active material, 5 wt% flake-type conductive material KS6 as a conductive material, 1 wt% styrene-butadiene rubber (SBR) as a binder, and 1 wt% carboxymethyl cellulose (CMC) as a thickener. A cathode was manufactured by coating, drying, and pressing the cathode slurry onto a copper substrate.
[0150] As described above, the anode and cathode manufactured were each laminated by performing a predetermined notching, and a separator (polyethylene, thickness 25 μm) was interposed between the anode and cathode to form an electrode cell, after which the tab portions of the anode and cathode were welded. The welded combination of anode / separator / cathode was placed inside a pouch, and three sides were sealed, excluding the surface for injecting the electrolyte. At this time, the portion containing the electrode tabs was included in the sealed portion. Electrolyte was injected through the remaining surface excluding the sealed portion, and after sealing the remaining surface, the mixture was impregnated for at least 12 hours.
[0151] The electrolyte used was prepared by dissolving 1M LiPF6 in a mixed solvent of EC / EMC / DEC (25 / 45 / 30; volume ratio) and then adding 1 wt% vinylene carbonate (VC), 0.5 wt% 1,3-propensulfone (PRS), and 0.5 wt% lithium bis(oxalateto)borate (LiBOB).
[0153] Experimental Example 1: Measurement of Electrode Density
[0154] In the anode manufactured by performing a roll press at a pressure of 20 MPa, the electrode density was measured by dividing the weight of the anode active material layer by the volume of the anode active material layer.
[0155] The measurement results are shown in Table 2 below.
[0157] Experimental Example 2: Evaluation of Initial Discharge Capacity and Initial Efficiency
[0158] After charging the manufactured lithium secondary battery in a 25℃ chamber (CC / CV, rate limit 0.1 C, upper limit voltage 4.3V, 0.05C CUT-OFF), the battery capacity (initial charge capacity) was measured, and after discharging it again (CC 0.1C 3.0V CUT-OFF), the battery capacity (initial discharge capacity) was measured.
[0159] The initial capacity efficiency was evaluated by converting the value obtained by dividing the measured initial discharge capacity by the measured initial charge capacity into a percentage (%).
[0160] The evaluation results are shown together in Table 2 below.
[0162] Experimental Example 3: Evaluation of Lifetime Capacity Retention Rate
[0163] For the manufactured secondary battery, charging (CC / CV, 0.5C, 4.3V, 0.05C CUT-OFF) and discharging (CC, 1.0C, 3.0V CUT-OFF) at 45℃ were performed as one cycle, and the discharge capacity after one cycle was measured.
[0164] The life capacity retention rate was evaluated as a percentage of the value obtained by dividing the discharge capacity at 100 cycles by the discharge capacity at 1 cycle by the discharge capacity at 1 cycle by repeating the above cycle 100 times.
[0165] The evaluation results are shown in Table 2 below.
[0167] division Electrode density (g / cc) Electrochemical performance Initial discharge capacity (mAh / g) Initial efficiency (%) Lifespan Retention Rate @ 100 cycles (%) Example 1 3.66 211.5 89.9 92.2 Example 2 3.70 211.6 90.0 92.3 Example 3 3.67 211.5 89.8 92.0 Example 4 3.68 211.6 89.7 91.9 Example 5 3.71 204.6 90.8 93.8 Example 6 3.71 206.7 90.6 93.2 Example 7 3.70 208.2 90.2 92.9 Example 8 3.70 209.1 90.0 92.5 Example 9 3.71 214.8 89.7 91.9 Example 10 3.69 218.1 89.5 91.2 Example 11 3.68 221.7 89.1 90.8 Example 12 3.68 222.3 88.9 90.1 Example 13 3.67 211.5 89.6 91.5 Example 14 3.64 211.1 89.3 91.1 Example 15 3.63 211.1 89.4 91.0 Comparative Example 1 3.60 211.3 89.2 91.2 Comparative Example 2 3.65 211.0 89.3 91.7 Comparative Example 3 3.63 210.9 89.1 91.4 Comparative Example 4 3.62 210.7 89.1 91.0 Comparative Example 5 3.58 209.8 88.4 90.8 Comparative Example 6 3.55 209.3 88.3 90.5 Comparative Example 7 3.50 211.2 87.8 90.0
[0169] Referring to Tables 1 and 2 above, it can be seen that the lithium secondary battery according to the exemplary embodiments provides an overall higher electrode density compared to the comparative examples and has an excellent capacity retention rate.
[0170] In the cathodes for lithium secondary batteries according to the comparative examples, it is difficult to increase the electrode density to 3.66 g / cc or higher, and in order to provide the same capacity, the thickness of the electrode is increased compared to the examples, which may result in a lower energy density of the secondary battery. In this case, if the roll press process is performed with excessive pressure, the active material may break or structural collapse may occur, which may reduce electrochemical properties.
[0171] In addition, in the case of Comparative Examples 2 to 7, a second positive active material with low sphericity is included in excess and has a low average sphericity value. Accordingly, the structural stability of the positive active material is reduced, and cracking and collapse of the active material particles may occur due to high-voltage driving and repeated charging and discharging. Referring to Tables 1 and 2, it can be confirmed that the lifespan characteristics are degraded compared to the examples.
[0172] In the case of Examples 11 and 12, where the Ni molar ratio of the lithium metal oxide particles is 0.95 or higher, it can be seen that the initial charge / discharge capacity is improved, but the life retention rate is slightly reduced.
[0173] In the case of Example 14, where the difference in sphericity between the first positive active material and the second positive active material is less than 0.01, and Example 15, where the difference in sphericity is greater than 0.02, it can be confirmed that the electrode density and lifespan retention rate are somewhat reduced.
[0175] Experimental Example 4: Analysis of the surface of the cathode active material
[0176] Figures 4a and 4b are Scanning Electron Microscopy (SEM) images of the anode cross-section after 100 charge-discharge cycles of the lithium secondary battery according to Example 1 and Example 2, respectively.
[0177] FIGS. 5a to 5c are SEM images of the positive electrode cross-section after performing 100 charge-discharge cycles of lithium secondary batteries according to Comparative Examples 1 to 3, respectively.
[0178] Referring to FIGS. 4a and 4b, it can be seen that cracks and defects in the positive electrode active material particles are prevented in the positive electrode for a lithium secondary battery according to exemplary embodiments after repeated charging and discharging.
[0179] However, referring to FIGS. 5a to 5c, it can be seen that when repeated charging and discharging are performed on the positive electrodes for lithium secondary batteries according to Comparative Examples 1 to 3, cracks and breakage occur within the positive electrode active material particles. Explanation of the symbols
[0181] 100: Anode 105: Anode current collector 107: Anode Lead 110: Anode Active Material Layer 120: Cathode active material layer 125: Cathode current collector 127: Cathode Lead 130: Cathode 140: Separator 150: Electrode assembly 160: Case
Claims
Claim 1 A positive electrode active material for a lithium secondary battery comprising: a first positive electrode active material having a sphericity of 0.9 to 0.96; and a second positive electrode active material having a sphericity smaller than that of the first positive electrode active material and having a content smaller than that of the first positive electrode active material, wherein the average particle size (D50) of the second positive electrode active material is smaller than the average particle size (D50) of the first positive electrode active material, and the first positive electrode active material and the second positive electrode active material each independently comprise lithium metal oxide particles represented by the following chemical formula 1 or 2: [Chemical Formula 1]Li x Ni y M1 1-y O z [Chemical Formula 2]Li x Ni y M1 1-y M2 a O z (In the above chemical formulas 1 and 2, M1 is at least one element selected from the group consisting of B, Al, Si, Ti, V, Cr, Mn, Fe, Co, Cu, Zn, Y, Zr, Mo, Sn, and W, and 0 <x≤1.1, 0.8≤y≤0.98, 2.0≤z≤2.02이며, 화학식 2에서 M2는 Be, Mg, Ca, Sr, Ba 및 Ra로 구성된 그룹으로부터 선택되는 적어도 하나의 원소이고, 0.0002≤a≤0.02임). Claim 2 delete Claim 3 A positive electrode active material for a lithium secondary battery according to claim 1, wherein 0.8≤y≤0.95 in Formula 1. Claim 4 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the mixing weight ratio of the first positive electrode active material and the second positive electrode active material is 9:1 to 6:
4. Claim 5 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average sphericity of the positive electrode active material for a lithium secondary battery is 0.9 to 0.
96. Claim 6 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the sphericity of the second positive electrode active material is less than 0.
96. Claim 7 A positive active material for a lithium secondary battery according to claim 1, wherein the difference in sphericity between the first positive active material and the second positive active material is 0.01 or greater. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 7, wherein the sphericity of the first positive electrode active material is 0.95 to 0.96 and the sphericity of the second positive electrode active material is 0.9 to 0.
95. Claim 9 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material has a polycrystalline structure and the second positive electrode active material has a single crystal structure. Claim 10 delete Claim 11 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the first positive electrode active material is 8 to 20 μm. Claim 12 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size (D50) of the second positive electrode active material is 2 to 8 μm. Claim 13 A positive active material for a lithium secondary battery according to claim 1, wherein the first positive active material has a secondary particle structure and the second positive active material has a single particle structure. Claim 14 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the tap density is 3.66 g / cc or higher when pressurized at 20 MPa. Claim 15 A positive electrode for a lithium secondary battery comprising a positive electrode active material layer comprising the positive electrode active material for a lithium secondary battery according to claim 1. Claim 16 A positive electrode for a lithium secondary battery according to claim 15, wherein the electrode density of the positive active material layer is 2.5 to 4.0 g / cc. Claim 17 A lithium secondary battery comprising: a positive electrode including a positive electrode active material for a lithium secondary battery according to claim 1; and a negative electrode facing the positive electrode.
Citation Information
Patent Citations
Non-aqueous electrolyte lithium secondary battery
JP1995114942A
Electrode for battery, manufacturing method thereof, and battery
JP2009283353A
Active material sheet and electrode using same
KR1020140007268A
Positive electrode for lithium secondary battery and lithium secondary battery including the same
KR1020210019389A